Immanuel Wallerstein's Theory of the Capitalist World-System - Žiemelis, Darius (Lietuvos istorijos studijos, 2005)
One of the most significant tendencies in the development of Western historiography and social sciences in the last three decades has been the consolidation of a new multidisciplinary field of inquiry, comparative historical sociology (CHS). Reinhard Bendix, Charles Tilly, and Immanuel Wallerstein can be considered parents/creators of CHS in the U.S.A. The theory of the Capitalist World System (CWS), initiated by the American sociologist and historian I. Wallerstein (b. 1930), who started his career researching the contemporary history of Africa, is one branch of the CHS. This theory was formulated in opposition to Eurocentrism, which is characterized by a belief in the endless (linear) progress of European civilization and which discounts other (non-European) cultures. Wallerstein's popularity and influence in Western social sciences reached its zenith in the 1970s and 1980s, so that while perhaps coming late in the game, nonetheless knowledge and acquaintance with the ideas of this author can be useful for the conceptual renewal of modern Lithuanian historiography and for the investigation of problems in the socio-economic history of Central and Eastern Europe. The main strength of the CWS's approach is the possibility to expand historical thinking to regional and global perspectives in reply to the challenges facing social, political, and geopolitical reality and to interpret the history of every region in the historical context of local and world (meta) civilization.The main objectives of this article are: 1) to clarify the methodological traits and sources of the CWS's theory; 2) to reconstruct retrospectively the development of the CWS's theory in the works of Wallerstein (from the 16th to the second half of the 19th c.); 3) to discuss the critique and reception of CWS's theory.The subject of Wallerstein's study of CWS's theory is the origin and development of the capitalist world-system itself. CWS arose on the basis of the European world-economy during the "long" 16th century (1450-1640) and has been in existence ever since. CWS is an economic world based on capitalist production and division of labor, politically organized in the form of a union between sovereign and competing states. An especially important distinguishing feature of CWS is the differentiation into three economic zones: the core, the periphery, and the semi-periphery (according to their role in the world division of labor). The most important theoretical sources of CWS are dependency theory, F. Braudel's theory of history, K. Marx's theory of capitalism, and the Marxist theory of imperialism. Because of the dominant significance of Marxist sources, CWS can be considered a neo-Marxist theory.The development of the CWS's theory (from the 16th to the second half of the 19th c.) has three stages: 1) agrarian capitalism - the beginning of the CWS's theory; 2) mercantile capitalism - the outcome of the consolidation of the CWS's theory; 3) globalization period of the CWS.The critics of Wallerstein's theory of the CWS could be relatively differentiated into two groups - historians/sociologists based on Marxism and sociologists/ economists. The first group emphasizes that the theory of CWS is deficient in empirical adequacy, ignores the relationship between class structure and economic development, exaggerates the importance of the market on the internal socio-economic development of countries, and orients toward economism. Sociologists and economists notice that the theory does not analyze explicitly the influence of institutions on the emergence of capitalism and institutional development of the hierarchy of geo-economic zones.Synthesis of global and regional contexts investigating socioeconomic reality of the past could give higher empirical adequacy to the CWS's theory. On the other hand, the influence of the CWS's theory is confirmed by the further development of international political economy and radical renewal of cultural anthropology (not mentioning historical sociology).
Keywords: -